Geo-Congress 2019. selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, March 24-27, 2019, Philadelphia, Pennsylvania - Meehan, Christopher L.; Kumar, Sanjeev, 1964-; Pando, Miguel Angel, 1968-; Coe, Joseph T. (American Society of Civil Engineers, 2019)
Selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, held in Philadelphia, Pennsylvania, March 24-27, 2019. Sponsored by the Geo-Institute of ASCE. This Geotechnical Special Publication contains 30 peer-reviewed papers on embankments, dams, and slopes. Topics include: monitoring, evaluation, and rehabilitation of dams and levees; deformation analysis; landslides; monitoring, failure assessment, and rehabilitation of embankments; slope stability; and case histories. GSP 305 will be of interest to practitioners, academics, and policymakers in the area of dams, levees, and embankments
Keywords: Geotechnical engineering -- Congresses.; Geotechnical engineering -- Case studies.; Slopes (Soil mechanics) -- Congresses.; Dams -- Congresses.; Slopes (Soil mechanics) -- Case studies.; Dams -- Case studies.; elektronické knihy; electronic books